Relationship of environmental factors in pond water and dynamic changes of gut microbes of sea bass Lateolabrax japonicus - Zhu, Zheng; Xu, Yu-Min; Liang, Jun-Han; Huang, Wei; Chen, Jin-Ding; Wu, Si-Ting; Huang, Xiao-Hong; Huang, You-Hua; Zhang, Xiao-Yang; Sun, Hong-Yan; Qin, Qi-Wei (Frontiers in Microbiology, 2023)
The effect of structure of gut microbes on the health of host has attracted increasing attention. Sea bass Lateolabrax japonicus is an important farmed fish in China. The relationship of the dynamic changes of intestinal bacterial communities in L. japonicus and the cultural water environment is very important for healthy culture. Here, the diversity and abundance of the gut microbial communities of L. japonicus were evaluated during the culture using 16S rRNA Illumina sequencing. Both the opportunistic pathogens Aeromonas (1.68%), Vibrio (1.59%), and Acinetobacter (1.22%); and the potential probiotics Lactobacillus (2.27%), Bacillus (1.16%), and Lactococcus (0.37%) were distributed in the gut of L. japonicus. The increasing concentration of nitrogen of water environments with the increase of culture time significantly correlated with shifts in the microbial community structure: 40.04% of gut microbial changes due to nitrogen concentration. Higher concentrations of nitrogen showed a significantly negative correlation with intestinal probiotics in L. japonicus. The results indicate that the abundance of intestinal bacteria of L. japonicus is mainly driven by the changes of environmental factors (e.g., nitrogen), and it’s very important that the linking environmental parameters with bacterial data of guts could be used as an early warning indicator in L. japonicus heath culture.